Adjuvant Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors (TKIs) in Resected Non–Small Cell Lung Cancer (NSCLC): A Systematic Review and Meta-analysis. (May 2019) - Raphael, Jacques; Vincent, Mark; Boldt, Gabriel; Shah, Prakesh S.; Rodrigues, George; Blanchette, Phillip
Abstract : The role of adjuvant tyrosine kinase inhibitors (TKIs) in non–small cell lung cancer (NSCLC) is not well defined. Recent randomized controlled trials showed a disease-free survival (DFS) benefit in patients harboring an epidermal growth factor receptor (EGFR) mutation. Yet, older trials on patients with any EGFR status did not demonstrate the same benefit. We aimed to assess the efficacy and safety of adjuvant TKIs in NSCLC patients. The electronic databases Medline (PubMed) and EMBASE were searched for relevant randomized controlled trials. Random effect models were used. The primary outcome was DFS measured as hazard ratio (HR). The secondary outcomes were overall survival (OS) measured as HR, 2-year DFS and toxicity expressed as risk ratio and odds ratio (OR), respectively. Subgroup analyses assessed DFS by trial design. Six trials incorporating 1860 patients were included. In patients harboring an EGFR mutation, adjuvant TKIs decreased the risk of disease recurrence by 48% (HR: 0.52, 95% confidence interval [CI]: 0.35-0.78), improved 2-year DFS (HR: 0.53, 95% CI: 0.43-0.66) but did not improve OS (HR: 0.64, 95% CI: 0.22-1.89). The risk of developing ≥grade 3 skin toxicity (OR: 6.07, 95% CI: 4.34-8.51) and diarrhea (OR: 4.05; 95% CI: 2.44-6.74) was increased. In subgroup analyses, the DFS benefit was more pronounced in trials using TKIs over chemotherapy compared with trials using TKIs postchemotherapy. In conclusion, adjuvant TKIs decrease the risk of recurrence in NSCLC patients harboring an EGFR mutation but do not improve OS. Longer follow-up is needed for a definitive assessment of OS and to define the role of adjuvant TKI for NSCLC in the clinical practice. Abstract : Supplemental Digital Content is available in the text.